Pemilihan Bahasa dalam Ranah Publik Kaum Migran di Kota Semarang - Mujid Farihul Amin (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
Based on the results of this study it is known that in the public sphere most migrants in the city of Semarang use Indonesian more often than their mother tongue. However, it turns out that there are some migrants who still retain their native language, namely the traditional migrants who live in the villages. In the public sphere for migrants who are married and already working, in communicating with colleagues, superiors and subordinates more often use Indonesian in both official and informal situations. In the public sphere (such as schools and workplaces) for migrants with child status, most choose to use Indonesian to communicate well with peers, teachers, administrative staff, library staff, as well as gardeners and janitors.